Structural, Deployable Folds — Design and Simulation of Biological Inspired Folded Structures. (September 2014) - Baerlecken, Daniel; Gentry, Russell; Swarts, Matthew; Wonoto, Nixon
This paper presents a concept of folding as a form-generator for a structural system that allows the ability to deploy large spanning structures. The presented approach studies the embedded kinetic possibilities of folded structures and focuses on a parametric modeling process that allows structural performance evaluation of different types of the same origami family in order to optimize the geometry for a given scenario. The workflow between scripting based form generation – within Rhinoceros and Excel – and LS-DYNA is presented in detail. Additionally, within the context of an architectural project we discuss the question of scalability from a thin microstructure to a thickened roof structure.